Pengaruh Pemberian Ekstrak Etil Asetat Buah Biwa (Eriobotrya japonica (Tunb.) Lindl) Terhadap Profil Mikrobiota Usus Tikus Yang Diinduksi Escherichia coli - Lusiana, Diana Intan Gabriella; Hartanti, Yesiska Kristina; Andareas, Pangeran; Renjaan, Justina Andrea (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study investigated the therapeutic potential of ethyl acetate extract derived from Biwa fruit on the gut microbiota profile of E. coli-infected mice. This study used 30 BALB-C mice divided into five groups: positive control (Ciprofloxacin and Lomperamide 130 mg/kgBW), negative control (CMC-Na), and three Biwa extract treatment groups at doses of 200, 400, and 600 mg/kgBW. The findings demonstrated that Biwa extract at 200 mg/kgBW exhibited significant efficacy from day one, resulting in complete suppression of E. coli growth in mice. However, the cohort receiving 400 mg/kgBW showed recurring E. coli growth on day two, potentially attributable to contamination. This research provides promising preliminary evidence of the potential of Biwa fruit as an alternative herbal-based prebiotic therapy to overcome E. coli infection.